2012
DOI: 10.5352/jls.2012.22.2.148
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Trend in Blood Pressure and the Prevalence of Hypertension in Korean Adults

Abstract: A cross-sectional analysis of blood pressure (BP) changes and the current prevalence and distribution of hypertension among age groups in Korea were conducted. Systolic (SBP), diastolic (DBP), and pulse (PP) pressures were evaluated. Residents visiting a local Community Health Center for a health check-up and/or participating in the Health Promotion Program were included for the analyses. A total of 6,570 subjects (2,809 men, 3,761 women) were divided into five age groups: 30-39, 40-49, 50-59, 60-69, and 70≤ y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The prevalence of systolic hypertension was higher among men than women in the 60-74 year group, whereas that of diastolic hypertension was higher among women than men in the 80-90 year group. Lee and Lee (2012) have reported that the incidence of hypertension tended to increase with advancing age and was higher among men than among women. The Korean Society of Hypertension ( 2021) has reported lar results.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of systolic hypertension was higher among men than women in the 60-74 year group, whereas that of diastolic hypertension was higher among women than men in the 80-90 year group. Lee and Lee (2012) have reported that the incidence of hypertension tended to increase with advancing age and was higher among men than among women. The Korean Society of Hypertension ( 2021) has reported lar results.…”
Section: Discussionmentioning
confidence: 99%